Discourses of War: A Multimodal Analysis of the UNHCR’s Visual Representations of Refuges - Madiha Tahir; Attiya Khanam; Rashida Ahmad; Sarwat Jabeen (Corresponding Author) (Al-Qanṭara, 2023)
The present study explores the photographs of Ukrainian refuges on the website of UNHCR (United Nations Refugee Agency) to examine the visual grammar of the images, and to analyze the discursive representations and construction of refuges as a social actor, which conveys multiple meanings and ideologies to the masses. It also inquires the representational styles and regimes of visibilities dominant in the humanitarian aid discourses, in this case UNHCR, through the theoretical framework of multimodal critical discourse analysis (MCDA) by Machin (2007), along with insights from the cultural theory by Chouliaraki (2010, 2017). The analysis was conducted through observing the connotations, settings, poses, participants, social actors’ representation and modality of the selected visuals through purposive sampling. The social semiotic analysis of the data showed that constructed images were highly contextualized to portray a realistic coverage of the crisis. The refuges were infantilized and individualized to engage the viewers emotionally. Majority of the images exhibited “positive style” representation and the “visibilities of empathy” to summon viewers’ empathetic feelings, which ultimately encourage them towards more relief related activities.